The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13568-017-0326-0
|View full text |Cite
|
Sign up to set email alerts
|

Bulk isolation of basidiospores from wild mushrooms by electrostatic attraction with low risk of microbial contaminations

Abstract: The basidiospores of most Agaricomycetes are ballistospores. They are propelled off from their basidia at maturity when Buller’s drop develops at high humidity at the hilar spore appendix and fuses with a liquid film formed on the adaxial side of the spore. Spores are catapulted into the free air space between hymenia and fall then out of the mushroom’s cap by gravity. Here we show for 66 different species that ballistospores from mushrooms can be attracted against gravity to electrostatic charged plastic surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 87 publications
(149 reference statements)
0
9
0
Order By: Relevance
“…Coprinopsis atramentaria is studied for its ability to bioaccumulate 76 % of Cd 2+ , at a concentration of 1 mg L−1 of Cd 2+ , and 94.7% of Pb 2+ , at a concentration of 800 mg L−1 of Pb 2+ . Therefore, it has been documented as an effective accumulator of heavy metal ions for mycoremediation [ 132 ]. Park and his coauthors [ 133 ] reported that dead fungal biomass of Aspergillus niger, Rhizopus oryzae, Saccharomyces cerevisiae , and Penicillium chrysogenum could be used to convert toxic Cr (VI) to less toxic or nontoxic Cr (III).…”
Section: Bioremediation Capacity Of Microorganisms On Heavy Metalsmentioning
confidence: 99%
“…Coprinopsis atramentaria is studied for its ability to bioaccumulate 76 % of Cd 2+ , at a concentration of 1 mg L−1 of Cd 2+ , and 94.7% of Pb 2+ , at a concentration of 800 mg L−1 of Pb 2+ . Therefore, it has been documented as an effective accumulator of heavy metal ions for mycoremediation [ 132 ]. Park and his coauthors [ 133 ] reported that dead fungal biomass of Aspergillus niger, Rhizopus oryzae, Saccharomyces cerevisiae , and Penicillium chrysogenum could be used to convert toxic Cr (VI) to less toxic or nontoxic Cr (III).…”
Section: Bioremediation Capacity Of Microorganisms On Heavy Metalsmentioning
confidence: 99%
“…Coprinopsis atramentaria was studied for its ability to bioaccumulate 76% of Cd 2+ at a concentration of 1 mg/L of Cd 2+ , and 94.7% of Pb 2+ , at a concentration of 800 mg/L of Pb 2+ . Therefore, it has been documented as an effective accumulator of heavy metal ions for mycoremediation (Lakkireddy & Kües, 2017). Park and his coauthors (Park et al, 2005) reported that dead fungal biomass of A. niger, Rhizopus oryzae, Saccharomyces cerevisiae, and Penicillium chrysogenum could be used to convert toxic Cr (VI) to less toxic or nontoxic Cr (III).…”
Section: Fungi Remediation Capacity Of Heavy Metalmentioning
confidence: 99%
“…The fact that the fungal bioaerosol kept stable and no coagulation occurred can be explained by the electrostatic charge present on fungal spore surface. This charge prevents the spores from coagulation and coalescence [35]. The electrostatic charge and its relaxation time for 31 fungal species from basidiomycota division were measured by Saar et al [29]: the charge for the spores in the aerosol state was in a range of 21—981 electron changes (or (0.3 − 16.0) ⋅ 10 −17 C ) and decreased sevenfold within 47 minutes [29].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, collective aerodynamic properties of the spores were tailored by evolution, selecting those species which could spread their genetic material over larger areas [29]. The biologically induced electrostatic charge in the spores [29, 35] is just one of the many mechanisms that prevent aggregation and coagulation. The fungi have a variety of microbiological “tools” that serve for better aerosol stability, such as hydrophobins on the surface (for hydrophobicity) [33].…”
Section: Discussionmentioning
confidence: 99%